ANALISIS NILAI TAMBAH DAN PEMASARAN JAJAN TEMERODOK DI KECAMATAN SAKRA KABUPATEN LOMBOK TIMUR - Candra Yuli Apriliana; Dwi Praptomo Sudjatmiko; Sri Maryati (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2023)
This study aims to analyze the added value of the temerodok snack agro-industry in Sakra District, East Lombok Regency, analyze the channel and marketing efficiency of the temerodok snack agro-industry in Sakra District, East Lombok Regency, identify the problems faced in the temerodok snack agro-industry in Sakra District, East Lombok Regency. The method used is descriptive method by determining the sample area by purposive sampling. Respondents were determined by census and market participants were determined using snowball sampling. The data used are quantitative data and qualitative data. Data analysis used is production cost analysis, added value analysis, channel analysis and marketing efficiency. The results showed that the added value generated from the processing of glutinous rice flour into temerodok snacks is Rp.23.840,13/Kg of raw material with an added value ratio of 32,32%. The marketing channel for temerodok snacks in Sakra District uses two channels, namely channel I: Producer - Final Consumer and channel II: Producer - Retailer - Final Consumer with a sales volume from producer to final consumer of 325 Kg with a selling price of Rp.60.000,00/Kg and from retailers to final consumers as much as 136 Kg with a marketing margin of Rp.21.538,46/Kg, so that marketing channel I is more efficient. The marketing of temerodok snack products in Sakra District is fair and efficient from the calculation of the producer's share namely >60% and profit distribution >0.5. The main problems faced by the producers of the temerok agro-industry are fluctuating prices for other inputs (oil, eggs and sugar), lack of business capital and not utilizing social media, while the problems faced by market players are not utilizing social media and a lack of business capital. Keywords: Added Value, Temerodok Snacks, Marketing